(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: The corona virus disease 2019 (COVID-19) is a pandemic disease. Infection by COVID-19 in children is not so common but gradually the numbers of children affected with COVID-19 are increasing day by day. The epidemiological importance and clinical pattern in children with COVID-19 is now a challenge to be described by the clinicians. Objectives: To describe socio-demographic and clinical characteristics of COVID-19 infected children. Material and Methods: This cross sectional observational study was conducted among 58 COVID-19 children who were admitted in COVID-19 dedicated Kurmitola General Hospital (KGH), Dhaka from March 2020 to July 2020. Their signs, symptoms, sex, age distribution, laboratory results and familial contact were analyzed. Results: Among 58 most of the children (63.8%) were in school going age (5-15years). The number of female (39) was more than male (19) and female-male ratio was 1:0.48. Most of the children (75.9%) came from urban lower middle socioeconomic group. About 84.4% children were affected from family member. Among all, (8.6%) patients had no symptoms. Main symptoms of the children were cough (36.2%), only fever (22.4%), fever with cough (8.62%) and diarrhoea (5.2%). About 12.06% of the children had additional symptoms including sore throat, nasal congestion, fatigue, headache, body ache, vomiting, abdominal pain, convulsion and rash, 6.9% had respiratory distress and one child came with convulsion. About 12.1% patients showed lymphopenia, 18.9% showed leucopenia, 13.8% patient had neutrophillia. C-Reactive Protein (CRP) and serum ferritin were high in only 12.1% and 8.6% cases respectively. There were 29.3% patients who had normal Chest X-Ray and 58.6% had mild lesion, 8.6% had bilateral consolidation and 3.4% had patchy opacities. Conclusions: COVID-19 is not so common in children and usually presents with mild form or no sign symptoms clinically and by laboratory analysis. But it is noteworthy that they may play role in transmission of disease. JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 72-75